2021
DOI: 10.1029/2021ef002249
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Recent North Pacific Decadal Variability: The Role of Aerosol Forcing

Abstract: Climate variability in the Pacific has an important influence on climate around the globe. In the period from 1981 to 2012, there was an observed large‐scale cooling in the Pacific. This cooling projected onto the negative phase of the Pacific Decadal Oscillation (PDO) and contributed to a slowdown in the rate of near‐surface temperature warming. However, this cooling pattern is not simulated well by the majority of coupled climate models and its cause is uncertain. We use large multi‐model ensembles from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 61 publications
(106 reference statements)
9
35
0
Order By: Relevance
“…However, aerosol effects are much more heterogeneous both in time and space, due to strong regional patterns of emission changes and indirect effects through interactions with clouds. Many studies have shown potential anthropogenic aerosol impacts on decadal climate including AMV (Booth et al, 2012;Bellucci et al, 2017;Murphy et al, 2017;Bellomo et al, 2018;Watanabe and Tatebe, 2019), Atlantic Meridional Overturning Circulation (AMOC, Menary et al, 2020;Hassan et al, 2021), the Aleutian Low and Pacific Decadal Variability (PDV, Allen et al, 2014;Takahashi and Watanabe, 2016;Oudar et al, 2018;Wilcox et al, 2019;Dittus et al, 2021;Dow et al, 2021), mid-latitude atmospheric jets (Wang Y. et al, 2020;Dong et al, 2022), southern hemisphere atmospheric circulation (Gillett et al, 2013;Rotstayn et al, 2013;Wang H. et al, 2020), Atlantic hurricanes (Mann and Emanuel, 2006;Dunstone et al, 2013), Sahel rainfall (Ackerley et al, 2011;Marvel et al, 2020;Hirasawa et al, 2022), and monsoon rainfall (Bollasina et al, 2011;Polson et al, 2014;Ma et al, 2017;Zhou et al, 2020), though aerosol indirect effects are particularly uncertain and these links are still debated (Oudar et al, 2018;Zhang R. et al, 2019;Baek et al, 2022).…”
Section: Potential Drivers Of Multi-annual To Decadal Changes In Climatementioning
confidence: 99%
“…However, aerosol effects are much more heterogeneous both in time and space, due to strong regional patterns of emission changes and indirect effects through interactions with clouds. Many studies have shown potential anthropogenic aerosol impacts on decadal climate including AMV (Booth et al, 2012;Bellucci et al, 2017;Murphy et al, 2017;Bellomo et al, 2018;Watanabe and Tatebe, 2019), Atlantic Meridional Overturning Circulation (AMOC, Menary et al, 2020;Hassan et al, 2021), the Aleutian Low and Pacific Decadal Variability (PDV, Allen et al, 2014;Takahashi and Watanabe, 2016;Oudar et al, 2018;Wilcox et al, 2019;Dittus et al, 2021;Dow et al, 2021), mid-latitude atmospheric jets (Wang Y. et al, 2020;Dong et al, 2022), southern hemisphere atmospheric circulation (Gillett et al, 2013;Rotstayn et al, 2013;Wang H. et al, 2020), Atlantic hurricanes (Mann and Emanuel, 2006;Dunstone et al, 2013), Sahel rainfall (Ackerley et al, 2011;Marvel et al, 2020;Hirasawa et al, 2022), and monsoon rainfall (Bollasina et al, 2011;Polson et al, 2014;Ma et al, 2017;Zhou et al, 2020), though aerosol indirect effects are particularly uncertain and these links are still debated (Oudar et al, 2018;Zhang R. et al, 2019;Baek et al, 2022).…”
Section: Potential Drivers Of Multi-annual To Decadal Changes In Climatementioning
confidence: 99%
“…Menary et al (2020) find the AMOC has increased in CMIP6 historical simulations compared with CMIP5, which they attribute to stronger aerosol forcing on average in the CMIP6 models. Robson et al (2022) further find a link between AMOC strengthening and increased AA forcing within CMIP6 models, linked to enhanced surface heat loss in the sub-polar North Atlantic.…”
Section: Introductionmentioning
confidence: 59%
“…The SAT regression in 1981-2012 resembles a negative Pacific Decadal Oscillation, and this link is investigated in Dittus et al (2022) in both the SMURPHS ensemble and other CMIP6 GCMs. They conclude that AA can induce an increase in North Pacific sea-level pressure (SLP) which promotes a negative PDO in this time period.…”
Section: Zonally Integrated Ocean Heat Content Trendsmentioning
confidence: 99%
“…Olonscheck et al (2020) showed that the observed East-West Pacific gradient (which projects strongly onto an IPO/PDO like pattern) was very much anomalous (captured by only a tiny minority of initial condition ensembles). There are open questions about what drove this observed pattern, ranging from a particular extreme mode of variability (Watanabe et al 2021), evidence of model error in tropical Pacific SSTs and the cold tongue (Seager et al 2019), externally driven by either anthropogenic aerosols (Dittus et al 2021) or volcanoes (Gregory et al 2020). This anomalous Pacific SST response (from the 1950s, but especially over the hiatus period) may be another factor why the ensemble mean response (which does not capture this Pacific SST shift) and the reanalysis precipitation trends (which do capture this) do not agree.…”
Section: Resultsmentioning
confidence: 99%
“…Others have also recently showed that the remote effects of AAs are likely related to the generation of Rossby waves, including from East Asia (Wilcox et al 2019). This also includes AA-induced weakening of the Aleutian Low (Dittus et al 2021) via a Rossby wave teleconnection, as well as BC from East Asia/India (Dow et al 2021).…”
Section: Discussionmentioning
confidence: 98%